THE INFLUENCE OF STARTER VOLUME AND AIR FLOWRATE IN HOSPITAL WASTE WATER TREATMENT USING AEROBIC FIXED FILM BIOFILTER BATCH (AF2B) REACTOR (Jurnal Bahan Alam Terbarukan, 2017)
BOD, COD, phenol and ammonia-free in the effluent of hospitals wastewater often exceed the quality standards. This was due to less optimal biological processes to degrade the pollutants. So we need an efforts to find optimal process conditions through the engineering process and the factors that affect the biodegradation of pollutants. On the other hand, AF2B reactor containing biofilter with bee nest shaped has a large specific surface area so as to maximize the biodegradation process of pollutants by microorganisms. While bacteria consortium consisting of several types of bacteria have a greater capacity than a single bacterium in the degradation of pollutants. The research aims to determine the effect of starter volume and air flowrate to decrease the concentration of pollutants (BOD, COD, phenol and ammonia-free) in AF2B reactor batch using a bacterial consortium. The research was conducted in three phase which are the making of growth curve, acclimatization and biodegradation of pollutants in an AF2B reactor batch using a bacterial consortium. The experiment variables are the starter volume (85%, 75%, 65% in volume), and the air flowrate (2.5; 5; and 7.5 liter/min). Materials used are hospital waste water and bacterial consortium. The experiment begins with setting up the AF2B reactor containing biofilter with bee nest shaped and then filled it with a starter from the acclimatization process on a given volume and followed by supplies of air at a certain flowrate. Then hospital waste water and 5% of nutrients were added till reach 10 liters of total volume in reactor. Samples were taken every 30 minutes for up to 360 minutes of biodegradation process. The samples were then analyzed its pollutants concentration (BOD, COD, phenol and ammonia-free). The BOD concentration was analyzed using Winkler bottles method, COD using open reflux method, while phenol and ammonia-free using UV-Vis spectrophotometry method. The results showed that the starter volume and air flowrate affect the decrease of pollutants concentration till reach quality standard, which at starter volume of 85%, air flowrate of 7.5 liter/min and biodegradation time of 360 min can reduce the BOD, COD, phenol, and ammonia-free to 92%, 86%, 88% and 76% respectively.